Requirement of Succinate for the Growth of Vibrio succinogenes - Niederman, R. A. (1972)
Vibrio succinogenes required relatively small amounts of succinate for growth when formate plus nitrate was supplied as the energy source. The requirement for succinate was not apparent when formate plus fumarate was the energy source because fumarate is reduced to succinate. l-Asparagine, fumarate, and malate replaced succinate, and it appears likely that they do so by being converted to succinate. Formate plus l-aspartate or l-asparagine served as energy sources for growth. The stoichiometry of the reduction of aspartate with H(2) by resting cells suggests an aspartase reaction followed by reduction of fumarate to succinate. Oxalacetate or pyruvate plus bicarbonate did not substitute for succinate, nor did many other compounds that were tested. (14)C-succinate was mainly incorporated into the alcohol-soluble fraction of cells, although there was significant incorporation into the hot trichloroacetic acid-soluble and -insoluble fractions.